2021
DOI: 10.1109/tdei.2020.009153
|View full text |Cite
|
Sign up to set email alerts
|

Property Failure of Silicone Rubber Caused by Silicone Grease Absorption

Abstract: This study focuses on the absorption characteristics and evolution of key properties of silicone rubber (SiR) in the presence of silicone grease; a typical material used in power cable accessories. Diffusion mechanism of silicone grease within the SiR is investigated and the results indicate that it follows Langmuir diffusion model in the absence of significant swelling. Silicone grease absorption behavior is also explored under tensile strain and at various temperatures. The tensile strain accelerates and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…It can also be found that the SiR reaches the swelling equilibrium when the mass increases to about 7%, which is consistent with the experimental results of 1000 cSt silicone oil in Ref. [23].…”
Section: Resultssupporting
confidence: 91%
“…It can also be found that the SiR reaches the swelling equilibrium when the mass increases to about 7%, which is consistent with the experimental results of 1000 cSt silicone oil in Ref. [23].…”
Section: Resultssupporting
confidence: 91%